Quantitative Determination of Whey Protein to Casein Ratio in Infant Formula Milk Powder - Xu, Tao; Chen, Jingyao; Yang, Kai; Qiao, Weicang; Zhao, Junying; Chen, Lijun (Frontiers in Chemistry, 2022)
This study was aimed to establish a method for quantitatively determining the ratio of whey protein in the total protein of infant formula by respectively selecting two characteristic peptides from whey protein and casein and calculating the ratio between the characteristic peptides. A nanoliter high-performance liquid chromatography tandem high-resolution mass spectrometry (Q Exactive) was used to simultaneously detect the characteristic peptides of two main whey proteins and two main caseins. The characteristic peptides were calculated, predicted, and screened using the ExPASy website, and peptide information was confirmed by database retrieval after the analysis by using a high-resolution mass spectrometer. The matrix effect was compensated by comparing the characteristic peptides in whey protein with those in casein protein, in which isotope internal standards were not required. The influence of the changes of the protein content in whey protein and casein on the detection method was eliminated by the calculation formula designed by ourselves. In this detection method, the sample was stable in the total protein concentration range of between 0.1 and 0.4 mg/ml. In the simulated industrial processing environment, with desalted whey powder, the recovery rate was 98.63–113.33% under different spiked levels with good reproducibility (RSD<8%). The RSDs of intraday and interday precisions were 2.03–9.35% and 0.61–11.02%, respectively. The different processing procedures of samples had no significant impact on the detection of whey protein (RSD% for milk samples treated by different processing techniques was 2.97%). The quantitation method of whey protein was applied to evaluate the whey protein content in different brands of commercially available milk powder. In summary, the proposed method was applicable for quantitative analysis of whey proteins in the infant formula.